저압용 방수 콘센트의 개발 및 평가에 관한 연구 - 崔忠錫(Chung-Seog Choi); 金昌性(Chang-Soung Kim) (전기학회 논문지 P권, 57(2), 2008)
In this paper, we investigates accident actual conditions of electric outlet for low voltage that is used into interior and clear hazardous factor. Electric outlet for general can know that melting of socket-outlet and carbonization of support occur if a contaminant becomes burnout because is flowed in. Existent outlet consists of structure that special quality is good but inflow of a contaminant is easy when is dry. But, waterproof outlet passes silicon layer and have connected structure plug. As developed outlet covers whole surface and back side, interval was shut. Safety pin of developed outlet was established to operate to vertical direction. Therefore, we estimate that contribute on prevention of electrical disaster if use developed outlet to a restaurant, a laundry, a laboratory etc.